Lithium bioleaching: An emerging approach for the recovery of Li from spent lithium ion batteries. (August 2021) - Moazzam, Parisa; Boroumand, Yasaman; Rabiei, Parisa; Baghbaderani, Sorour Salehi; Mokarian, Parastou; Mohagheghian, Fereshteh; Mohammed, Layth Jasim; Razmjou, Amir
Abstract: The rapidly growing demand for lithium has resulted in a sharp increase in its price. This is due to the ubiquitous use of lithium-ion batteries (LIBs) in large-scale energy and transportation sectors as well as portable devices. Recycling of the LIBs for being the supply of critical metals hence becomes environmentally and economically viable. The presently used approaches for the recovery of spent LIBs like pyrometallurgical process can effectively recover nickel, cobalt, and copper, while lithium is usually lost in slag. Bioleaching process as an alternative method of extraction and recovery of valuable metals from the primary and secondary resources has been attracting a large pool of attraction. This method can provide higher recovery yield even for low concentration of metals which makes it viable among conventional methods. The bioleaching process can work with lower operating cost and consumed water and energy along with a simple condition, which produces less hazardous by-products ultimately. Here, we comprehensively review the biological and chemical mechanisms of the bioleaching process with a conclusive discussion to help how to extend the use of bioleaching for lithium extraction and recovery from the spent LIBs with a focus on recovery yields improvement. We elaborate on the three main types of the reported bioleaching with considering effective parameters including temperature, initial pH, pulp density, aeration, and medium and cell nutrients to sustain microorganism activity. Finally, practical challenges and future opportunities of lithium are discussed to inspire future research trends and pilot studies to realize the full potential of lithium recovery using sustainable bioleaching processes to extend a clean energy future. Graphical abstract: Image 1 Highlights: We review the process of the bioleaching for Li recovery as a cleaner and more economical method. The bioleaching shows great potential to effectively recover Li from the secondary resources. Slow kinetics and selective recovery challenged the industrial scale of bioleaching. Process design factors and microorganism genome engineering should be the focus of future research direction.